Chemical similarity between Dictyota caribaea and Dictyota menstrualis (Dictyotaceae, Phaeophyceae) from the coast of Rio de Janeiro, Brazil. (February 2015) - Farias de Mesquita, Michelle Marchezan; Baddini, Ana Luísa de Queiroz; Pereira Netto, Annibal Duarte; Magalhães de Araujo, Juliana; Salgueiro, Fabiano; Lopes Filho, Erick Alves Pereira; De-Paula, Joel Campos; Fleury, Beatriz Grosso; Cavalcanti, Diana Negrão; Teixeira, Valéria Laneuville
Highlights: The chemical similarity between two Southeastern Brazilian Dictyota species is proposed: Dictyota caribaea and Dicyota menstrualis. The two species are observed in the South American Tropical areas. D. caribaea and D. menstrualis produce pachydictyol A, dichotomanol, dichotomol acetate and cycloxenianol acetate diterpenes. Molecular biology confirms the chemical results.